Pengaruh Investasi dan Upah Terhadap Penyerapan Tenaga Kerja Pada Sektor Industri Pengolahan Provinsi Sumatera Utara - Nadiyah Mawaddah; Noni Rozaini (Madani: Jurnal Ilmiah Multidisiplin, 2023)
High labor absorption will contribute to one of the important influencing factors, namely investment and wages. This study aims to analyze the effect of investment and wages on employment in North Sumatra. The data used is secondary data obtained from the central statistics agency from 2006 to 2020. The analytical method used is multiple regression. The results of the study show that investment has a positive but not significant effect on employment.Â